2023
DOI: 10.1002/dad2.12388
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength, gait speed, and trajectories of cognitive function in community‐dwelling older adults: A prospective study

Abstract: Introduction This study investigated whether grip strength and gait speed predict cognitive aging trajectories and examined potential sex‐specific associations. Methods Community‐dwelling older adults ( n = 19,114) were followed for up to 7 years, with regular assessment of global function, episodic memory, psychomotor speed, and executive function. Group‐based multi‐trajectory modeling identified joint cognitive trajectories. Multinomial logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Recent study involving more than 19,000 community-dwelling older adults observed that gait speed was positively related to the likelihood of high cognitive trajectories and negatively with the risk of low cognitive trajectories. This result suggests that gait speed was a stringer predictor of cognitive decline trajectory in men [ 30 ]. The walking ability is a valuable predictor of functional decline in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study involving more than 19,000 community-dwelling older adults observed that gait speed was positively related to the likelihood of high cognitive trajectories and negatively with the risk of low cognitive trajectories. This result suggests that gait speed was a stringer predictor of cognitive decline trajectory in men [ 30 ]. The walking ability is a valuable predictor of functional decline in older adults.…”
Section: Discussionmentioning
confidence: 99%